Future Competencies of Non-Formal Education Students - Dewi Rahmawaty,; Fitri Yolanda,; Nadiroh,; Faiz Ayatuloh,; Revi Mainaki,; Dikdik Hidayatuloh,; Maya Gayatri,; Salwa Mufida, (Edumaspul: Jurnal Pendidikan, 2026)
Education plays a crucial role in the development and progress of a nation. With advances in science and technology, globalization and the internationalization of education are considered challenges that every country must face. One of the key challenges in education today is the lack of future competencies among students. However, the reality also shows that there are high numbers of school dropouts, unschooled youth, and even individuals who have not attended formal education. Consequently, individuals who do not attend formal education experience difficulties in understanding and learning future competencies that will enable them to face competition. To address the challenges posed by global change and the knowledge economy, countries around the world, including Indonesia, have introduced and implemented alternatives to help individuals acquire education through non-formal education. This study was conducted to determine the Future Competenciess of LKP students throughout Indonesia. A total of 150 LKP students in Indonesia participated in this study using a descriptive survey method. The results showed that LKP students have a low level of mastery of Future Competenciess. Furthermore, the results of the independent sample t-test and one-way ANOVA test revealed that gender, age, and employment status influenced students' mastery of Future Competenciess.